Training of Computer-Based Qomariah Month Initial Determination (a Case Study of Determination the Months of Ramadhan, Syawwal, and Dzulhijjah) in Nurul Ikhlas Mosque, Bengkulu City, Bengkulu Province, Indonesia - Arif Ismul Hadi; Refrizon Refrizon; Budi Harlianto; Darmawan Ikhlas Fadli; Isfardian Agustin Awaliyah; Nur Husniatin Kamila (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The determination of the initial of the Qomariah month is still a difference, especially in determining the initial of Ramadhan, Syawwal, and Dzulhijjah. This can happen because there are differences in the method of determination. The method is in the form of Hisab method and Rukyat method. The purpose of community service activities is to determine the initial of the month of Qomariah based on MABIMS criteria (agreement of the Minister of Religion of Brunei Darussalam, Indonesia, Malaysia, and Singapore on 27-29 June 2012 in Bali) and determine the initial of the month using computer software in the form of Accurate Hijri Calculator (AHC) ver. 2.2.1. The method used in this activity is lecture, practice, and discussion. Based on AHC software application ver. 2.2.1 shows that according to calculation 1 Ramadhan falls on Saturday April 2, 2022, but according to MABIMS criteria it falls on Sunday April 3, 2022. This is a possible difference in the start time of fasting in 2022 in Indonesia. However, for 1 Syawwal, both the calculation and the MABIMS criteria fall on the same day, Monday May 2, 2022, both in Indonesia and in other countries.